What a Difference a Month Makes: Stock Analyst Valuations Following Initial Public Offerings - Houston, Joel; James, Christopher; Karceski, Jason (Journal of Financial and Quantitative Analysis, 2006)
Abstract We examine how analysts establish target prices for IPO firms and whether comparable firms used to support target prices are helpful in explaining IPO offer prices. During the bubble period of 1999 to 2000, the average offer price was set at a discount relative to comparable firm valuations. In contrast, the average offer price was set at a small premium relative to comparables in the pre-bubble period. This shift appears to hold even after controlling for the differences in the types of firms going public during the bubble period. Moreover, target prices of IPO firms were set at a higher premium relative to comparables during the bubble period. While our results suggest that underwriters systematically discounted offer prices during the bubble period, an alternative explanation is that the shift arose because underwriters and analysts faced different incentives and legal exposures during the bubble period.